HALUSINASI PADA PASIEN MENINGITIS STREPTOCOCCUS SUIS - Wahju Handojo Setiawan,* Anak Agung Raka Sudewi,* Ida Ayu Sri Wijayanti,* Ni Ketut Sri Diniari** (Neurona Majalah Kedokteran Neuro Sains, 2016)
REPORTED A 51 YEARS OLD MALE WITH DECREASE LEVEL OF CONSCIOUSNESS WITH HIGH FEVER AND INFECTION OF THE LUNG AND DEVELOPED PARTIAL SECONDARY GENERALIZED SEIZURE CEREBROSPINAL FLUID EXAMINATION SHOWED ELEVATED CELLS AND PROTEIN LEVEL AND DECREASED OF BLOODLIQUOR GLUCOSE LEVEL RATIO BLOOD CULTURE WAS POSITIVE FOR STREPTOCOCCUS SUIS TYPE II PATIENT WAS GIVEN ANTIBIOTICS FOR 14 DAYS AND BECAME BETTER AFTERWARDS BUT DEVELOPED DEAFNESS AND HAD TACTIL AND AUDITORY HALLUCINATIONS AS PART OF THE COMPLICATIONS